A novel systemic inflammation response index (SIRI) for predicting the survival of patients with pancreatic cancer after chemotherapy. Issue 14 (6th May 2016) - Qi, Qi; Zhuang, Liping; Shen, Yehua; Geng, Yawen; Yu, Shulin; Chen, Hao; Liu, Luming; Meng, Zhiqiang; Wang, Peng; Chen, Zhen
Abstract : BACKGROUND: Predicting survival is uniquely difficult in patients with pancreatic cancer who receive chemotherapy. The authors developed a systemic inflammation response index (SIRI) based on peripheral neutrophil, monocyte, and lymphocyte counts and evaluated the ability of the SIRI to predict the survival of patients with pancreatic cancer who received chemotherapy. METHODS: The SIRI was developed in a training set of 177 patients who had advanced pancreatic cancer and received palliative chemotherapy. The ability of the SIRI to predict a patient's survival after chemotherapy was validated in 2 independent cohorts (n = 397). RESULTS: Compared with patients who had an SIRI <1.8, patients in the training cohort who had an SIRI ≥1.8 had a shorter time to progression (TTP) (hazard ratio [HR], 2.348; 95% confidence interval, 1.559‐3.535; P = .003) and shorter overall survival (OS) (HR, 2.789; 95% confidence interval, 1.897‐4.121; P < .001). Comparable TTP and OS findings were observed in 2 independent validation cohorts. Multivariate analysis confirmed that the SIRI was an independent prognostic factor for both TTP and OS. In addition, compared with no change, an increase in the SIRI at week 8 was associated with poor TTP and OS, whereas a decrease in the SIRI was associated with improved outcomes. In addition, high SIRI scores were correlated with higher serum levels of interleukin 10, C‐C motif chemokine ligand 17 (CCL17), CCL18, and CCL22 and with a shortened TTP. CONCLUSIONS: The SIRI can be used to predict the survival of patients with pancreatic adenocarcinomas who receive chemotherapy, potentially allowing clinicians to improve treatment outcomes by identifying candidates for aggressive therapy. Cancer 2016;122:2158–67 . © 2016 American Cancer Society . Abstract : The authors describe their development of a systemic inflammation response index based on peripheral neutrophil, monocyte, and lymphocyte counts. The index can be used to predict the survival of patients with pancreatic adenocarcinoma who receive chemotherapy.